Application of monodisperse oxide nanoparticles in solid oxide electrolytic tank
The monodispersed cerium oxide nanoparticles n-hexane solution was prepared by thermal decomposition, which solved the problems of instability of electric-ion transport and reduced reaction gas diffusion rate in CO2 electrolysis reaction, and achieved efficient CO2 electroreduction reaction and extension of electrode life.
Patent Information
- Application Number
- CN202510011532.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-04
- Publication Date
- 2025-04-15
AI Technical Summary
The existing SOEC electrode materials have problems such as instability in the CO2 electrolysis reaction of electric-ion transport and reduced diffusion rate of the reaction gas, resulting in low electrochemical performance.
The monodispersed cerium oxide nanoparticles n-hexane solution was prepared by thermal decomposition method, and the nanoparticles were monodispersed in a non-polar solvent using surfactant to achieve uniform penetration of the nanoparticles into the electrode channel, and a uniform nano-scale three-phase interface was constructed through a single/two dipping and roasting step.
It significantly improves the electrochemical reaction performance of SOEC electrodes, improves the catalytic efficiency of CO2 electroreduction reaction, and extends the electrode life.
Smart Images

Figure CN119824459A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to the application of monodisperse oxide nanoparticles in a solid oxide electrolytic cell (SOEC). Background Art
[0002] With the continuous development of the world's industry, the massive consumption of fossil fuels by humans has led to a continuous increase in the concentration of CO2 in the atmosphere, causing the greenhouse effect to become increasingly serious. Climate change has brought very severe challenges to our lives. How to realize the resource utilization of CO2 is one of the main environmental problems currently facing my country's environmental field. At the same time, in order to reduce environmental pollution and reduce dependence on foreign fossil energy supply, it is urgent to gradually adjust the energy structure and vigorously develop renewable energy such as wind power, solar energy, and geothermal energy. However, the electricity provided by renewable energy is seasonal, intermittent, and volatile. Therefore, converting the electrical energy that cannot be consumed in time into chemical energy and storing it in the form of high-value-added chemical products is one of the important ways to convert and utilize renewable energy. In the context of carbon emission reduction and energy structure adjustment, an energy conversion and storage technology-solid oxide electrolysis cell (SOEC) has been proposed. This electrochemical technology process can use intermittent electrical energy and thermal energy to efficiently electrolyze CO2 and / or H2O, and store it in the form of chemical energy in H2, synthesis gas, hydrocarbon fuel or O2. This energy conversion technology can not only realize the high-value resource utilization of CO2 and convert it into high-value-added chemicals with high efficiency electrochemical conversion, but also provide an advanced energy storage method for intermittent output of renewable energy. Therefore, SOEC is one of the key technologies to help achieve the "dual carbon" goal and realize the large-scale and clean development of renewable intermittent energy systems.
[0003] SOEC has the advantages of high current density and high Faraday efficiency (above 95%). It can achieve efficient electrochemical reduction of CO2 at high temperature (600-850℃) and generate high value-added chemical CO. Since CO2 molecules are relatively stable, the electrochemical reduction of CO2 at the fuel electrode is the rate-controlling step in the entire reaction process. Therefore, improving the electrochemical performance of fuel electrode materials is a key breakthrough point in promoting the development of SOEC technology. In order to enable SOEC to have excellent power conversion efficiency, the core of improving the electrochemical performance of fuel electrode materials lies in the precise and stable construction of the electrode three-phase interface (gas, electrons, and ions) to achieve high-speed and stable transmission of electricity-ions inside the electrode material. To achieve this goal, nanostructure modification of traditional electrodes is one of the main research directions of SOEC electrode modification. By introducing nanoparticles with optimized characteristics of electricity-ion transmission and constructing a nanoscale gas-electron-ion three-phase conduction interface inside the electrode material, the contact sites between the reaction gas and the active electrons / ions can be greatly enriched, thereby greatly improving the CO2 electrolysis reaction performance of traditional electrode materials.
[0004] CeO2 nanoparticles have excellent catalytic performance, high surface area, unique oxygen ion conductivity and oxygen storage and release capacity, which can promote the adsorption, activation and conversion of reactants and have become an important material in various catalytic reactions. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) or (LSCM) Perovskite has attracted extensive attention due to its excellent doping ability, anti-carbon deposition ability and redox stability, and is currently the most widely used traditional electrode material. However, the current nano-modification strategy for traditional electrode materials still has great limitations. The current mainstream nano-electrode modification technology is mostly concentrated on the aqueous solution system impregnation method. Faced with the complex internal pore structure of perovskite electrodes, the high interfacial energy of aqueous solutions and the problem of easy agglomeration of nanoparticles make it difficult for metal salt precursors or nanoparticles to be uniformly loaded into the electrode pores. This uncontrollable distribution of nanoparticles will make the three-phase interface area constructed inside the electrode pores uneven, thereby isolating the newly added electric-ion transmission channels, or blocking the electrode pores, resulting in a decrease in the diffusion rate of the reaction gas, which greatly affects the performance and life of the electrolytic cell electrode. Although some scholars consider adding additives such as alcohol-based solvents and dispersants to reduce the interfacial energy of aqueous solutions, increase the charge stabilization effect or steric effect between particles to control the size of nanoparticles and the dispersion of particles in the electrode pores. However, it is often time-consuming, poorly controllable, not universally prepared, and has low efficiency in constructing the three-phase reactive interface, which has led to the fact that electrode nano-technology has not yet been widely used in the development of high-performance batteries, thus limiting its application in the field of SOEC. In view of the above problems, it is necessary to design the cerium-modified solution more accurately and effectively, so as to overcome the agglomeration of cerium oxide nanoparticles and obtain ultra-low interfacial energy. Summary of the invention
[0005] In view of the problem that the traditional impregnation strategy is difficult to achieve precise control of the nanoscale three-phase interface in the electrode due to the problems of easy agglomeration of nanoparticles and high interface energy of the solution, the present invention provides a strategy for impregnating modified SOEC fuel electrodes with monodisperse oxide nanoparticles, and uses it for CO2 electroreduction reaction; the method of the present invention prepares a monodisperse oxide nanoparticle n-hexane solution by thermal decomposition, drops the monodisperse oxide nanoparticle n-hexane solution onto the fuel electrode to immerse it in the fuel electrode, and after drying, calcines at 350-450°C for 1-2h to obtain an oxide nanoparticle-modified fuel electrode, and uses the modified fuel electrode in the electroreduction of CO2 in a solid oxide electrolyzer to improve the catalytic efficiency of the CO2 electroreduction reaction.
[0006] The invention synthesizes a monodisperse cerium oxide nanoparticle n-hexane solution by a thermal decomposition method. The cerium nanoparticles in the pre-synthesized monodisperse cerium oxide nanoparticle n-hexane solution are coated with a surfactant. The hydrophilic and lipophilic group structures of the surfactant make the cerium nanoparticles in the solution in a monodisperse state in a non-polar n-hexane solvent. The n-hexane solvent has an ultra-low interfacial energy (18 J / m 2 , 25℃; and the water solvent is 73J / m 2, 25°C) can make the cerium nanoparticles penetrate into the LSCF pores of the electrode uniformly and efficiently. At the same time, the surfactant encapsulating the cerium nanoparticles prevents the agglomeration of the particles through the steric hindrance effect, and effectively protects and prevents the sintering of the cerium nanoparticles during calcination.
[0007] Compared with the traditional aqueous solution impregnation method, the monodisperse nanoparticle n-hexane solution impregnation can cause the large-area cerium nanoparticle three-phase interface region to be evenly dispersed inside the electrode pores, and even reach the electrolyte interface (optimal active area) with only a single / twice impregnation and roasting step. Ultimately, the density of active sites at the three-phase interface inside the electrode is effectively increased, its dispersibility is optimized, and the electrochemical reaction performance is improved. In short, the method of the present invention has significant technical advantages in improving the electrochemical performance in the process of electroreduction of CO2.
[0008] The loading of oxide nanoparticles on the electrode is 0.19-0.56 mg / cm 2 .
[0009] The metal oxide nanoparticles of the present invention are monodisperse CeO2 nanoparticles. The monodisperse CeO2 nanoparticle n-hexane solution is prepared by stirring and mixing ammonium cerium nitrate, 1-octadecene and a surfactant in an inert atmosphere, treating at 175-185° C. for 1.5-2.5 hours, cooling to room temperature, adding anhydrous ethanol and centrifuging for 3-4 times, separating the solid from the liquid, washing the solid with anhydrous ethanol for 1-2 times, and dispersing the solid in an n-hexane solvent.
[0010] The surfactant is oleylamine, and the inert atmosphere is N2 or Ar gas.
[0011] The centrifugation is carried out using ethanol at 8000-10000 r / min for 5-10 min.
[0012] The fuel is a perovskite material, and the perovskite material is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ or La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3-δ The perovskite materials are conventional commercial products or referenced in the literature "La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3-δ The nanorods were prepared by the method described in "Study on the preparation of nanorods and their application in SOFC anode".
[0013] The present invention has the following beneficial effects:
[0014] By providing a strategy to modify the fuel electrode, the cerium oxide nanoparticles can evenly penetrate into the electrode pores and even reach the electrode pores near the electrolyte interface (optimal active area) with only a single / twice impregnation and calcination step. The traditional strategy requires 5-20 impregnation and calcination cycles for the same loading amount. Under the same reaction conditions, the impregnation modification method of the present invention exhibits higher electrochemical performance. The characterization results show that this method successfully prepares monodisperse CeO2 nanoparticles and can effectively improve the performance of SOEC electroreduction CO2 reaction.
[0015] The monodisperse CeO2 nanoparticle impregnation strategy not only breaks through the barriers of easy agglomeration of nanoparticles and high interfacial energy of solutions in traditional aqueous solution impregnation strategies to the greatest extent, but also realizes the precise and efficient construction of nanoscale three-phase interfaces with many advantages such as large macroscopic area and uniform dispersion of nanoparticles. More importantly, this strategy based on the "amphiphilic" properties of the surfactants on the outer layer of nanoparticles, the steric effect, and the ultra-low interfacial energy properties of the non-polar solvent n-hexane can be universally applied to the efficient and large-area immersion of a variety of nanoparticles into different types of SOEC fuel electrodes or air electrodes to construct a variety of types of nanostructured electrodes, breaking through the bottlenecks of the traditional strategy of using additives, such as time-consuming, poor controllability, inability to universally prepare, and low efficiency of three-phase reaction interface construction, providing a new strategy for constructing nanostructured electrodes for the widespread use of fuel electrode nanomaterials in the development of high-performance batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a TEM image of a n-hexane solution of monodispersed CeO2 nanoparticles in Example 1;
[0017] Figure 2 The SEM and TEM images of the fuel electrode prepared by immersing monodisperse CeO2 nanoparticles in n-hexane solution in Example 1;
[0018] Figure 3 This is the SEM image of the fuel electrode prepared by traditional Ce(NO3)3 aqueous solution immersion;
[0019] Figure 4 This is an IV comparison diagram of the electrode prepared by impregnation with CeO2 nanoparticle solution for electrolysis of CO2 in Example 1;
[0020] Figure 5 This is a comparison diagram of the constant pressure of the electrode prepared by impregnation with CeO2 nanoparticle solution for electrolysis of CO2 in Example 1;
[0021] Figure 6 This is a comparison chart of EIS of the electrode prepared by impregnation with CeO2 nanoparticle solution for electrolysis of CO2 in Example 1;
[0022] Figure 7This is the IV comparison diagram of the electrode prepared by impregnation with CeO2 nanoparticle solution for electrolysis of CO2 in Example 2. DETAILED DESCRIPTION
[0023] The technical scheme of the present invention is further described in detail below through examples, but the content of the present invention is not limited thereto. The methods in the present examples are conventional methods unless otherwise specified, and the materials and reagents used are obtained from commercial channels or prepared according to conventional methods unless otherwise specified;
[0024] Example 1: Preparation of monodisperse CeO2 nanoparticles and their application in solid oxide electrolysis cells
[0025] (1) Preparation of monodisperse CeO2 nanoparticles in n-hexane solution
[0026] Weigh 0.2741g of ammonium cerium nitrate in a three-necked flask, add 10mL of 1-octadecene (90%) and 0.9692mL of oleylamine, and place in an oil bath. After removing the air in the three-necked flask, under N2 atmosphere, the mixture is magnetically stirred for 30min, heated to 180°C and maintained for 2h, and after the reactants are cooled to room temperature, 30mL of anhydrous ethanol is added, and centrifuged at 8000r / min for 8 minutes. After repeated centrifugation 4 times, CeO2 nanoparticles are obtained by solid-liquid separation. After washing twice with anhydrous ethanol, 15mL of n-hexane is added to disperse the CeO2 nanoparticles to prepare a monodisperse CeO2 nanoparticle n-hexane solution. The CeO2 nanoparticle solution is determined by TGA thermogravimetric test to have a CeO2 nanoparticle solution concentration of 8.825mg / mL; TEM image of the monodisperse CeO2 nanoparticle solution is shown in Figure 1 , CeO2 nanoparticles are uniformly distributed spherical particles in the solution, with a particle size of about 5nm;
[0027] (2) Traditional electrode preparation
[0028] La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ 97% (mass ratio) of powder (LSGM, fuel cell materials) was added to 3% of PVB-ethanol mixture (prepared by mixing 6% PVB and 94% anhydrous ethanol), and the mixture was manually ground for 40 minutes. 0.2g of the ground mixture was added to a 15mm mold and placed in a tablet press. After being kept at a pressure of 6MPa for 2 minutes, it was calcined at 1450℃ in a muffle furnace for 5 hours to obtain an electrolyte disc with a diameter of 12mm.
[0029] According to the mass ratio of 6:4, take La 0.6 Sr 0.4 Co0.2 Fe 0.8 O 3-δ Powder (LSCF, Ningbo Suofer Energy Technology Co., Ltd.), added ethyl cellulose pinene alcohol mixture (mass ratio 5% ethyl cellulose and 95% pinene alcohol), the mixture was manually ground for 2 hours to make a fuel electrode slurry, the fuel electrode slurry was coated on one side of the electrolyte sheet by screen printing, dried at 80 ° C for 30 minutes, repeated coating 4 times, and calcined in a muffle furnace at 1050 ° C for 2 hours to make an electrode sheet fuel electrode;
[0030] According to the mass ratio of 7:3, La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ powder (LSCF, Ningbo Suofer Energy Technology Co., Ltd.) and (Ce 0.9 G 0.1 ) 1.95 (GDC) powder was mixed, and the mixture was mixed with ethyl cellulose pinene alcohol mixed solution (prepared by mixing 5% ethyl cellulose and 95% pinene alcohol by mass ratio) at a ratio of 6:4, and manually ground for 2 hours to prepare air electrode slurry, and the air electrode slurry was coated on the other side of the electrolyte sheet by screen printing, and baked in an oven at 80°C for 30 minutes. After repeating the coating 4 times, it was calcined in a muffle furnace at 1050°C for 2 hours to prepare the electrode sheet air electrode;
[0031] (3) Preparation of monodisperse CeO2 nanoparticle modified electrodes
[0032] After ultrasonicating the monodisperse CeO2 nanoparticle n-hexane solution for 10 minutes, use a 10μL pipette to drop the CeO2 nanoparticle solution onto the electrode sheet fuel electrode, 5μL each time, for a total of 6 times, with a total of 30μL. After drying in an oven at 80℃ for 30min, the electrode sheet was calcined in a muffle furnace at 400℃ for 1h. After calcination, the electrode sheet was repeatedly dripped with 30μL of CeO2 nanoparticle solution, 5μL each time, for 6 times, and then dried in an oven at 80℃ for 30min and calcined in a muffle furnace at 400℃ for 1h. The SEM and TEM images of the fuel electrode prepared by immersion of CeO2 nanoparticle solution are shown in Figure 2 ,From the figure, it can be seen that CeO2 nanoparticles are evenly distributed on the surface of the electrode sheet, even reaching the electrode pores near the electrolyte interface, and maintaining the nanoscale size (~5nm);
[0033] At the same time, the traditional Ce(NO3)3 aqueous solution was used to drip and impregnate the electrode as a control. According to the CeO2 nanoparticle concentration of 8.825 mg / mL, the CeO2 aqueous solution was prepared: 2226.4 mg of Ce(NO3)3·6H2O was weighed and dissolved in 100 mL of water to prepare a Ce(NO3)3 aqueous solution with a concentration of 22.264 mg / ml; the Ce(NO3)3 aqueous solution was ultrasonicated for 10 minutes, and then the electrode was prepared by dripping and impregnation according to the above method, except that the calcination temperature was 600℃ for 2 hours; the SEM image of the fuel electrode prepared by immersion in Ce(NO3)3 aqueous solution is shown in Figure 3 , CeO2 particles are unevenly distributed and show obvious agglomeration;
[0034] (4) Electroreduction of CO2 in solid oxide electrolysis cells
[0035] Step (3) After the electrode disc is calcined, silver paste is brushed on the fuel electrode and the air electrode as a current collecting layer, and baked in an oven at 150°C for 30 minutes. Silver wire is used as a conductor for the fuel electrode and the air electrode. The prepared electrode disc is placed at one end of a ceramic tube with the fuel electrode facing inward and in contact with the gas in the tube, and the air electrode is exposed to the air, and sealed with ceramic glue;
[0036] After N2 was purged at the other end of the ceramic tube, N2 containing 95% CO2 was introduced into the ceramic tube as the raw gas, and the electrolysis of CO2 was carried out at the fuel electrode. The raw gas flow rate was 30 mL / min, and the temperature was increased to 800°C at 3°C / min for testing;
[0037] The IV test results are shown in Figure 4. It can be seen from the figure that the electrode prepared by the method of the present invention exhibits a higher current density, which is as high as 3.18A·cm at 800℃ and 1.6V. -2 , which is significantly higher than the current density of traditional aqueous solution immersion.
[0038] The constant pressure test results are shown in Figure 5 Under the voltage conditions of 1.1V, 1.2V, 1.3V, 1.4V and 1.5V, the electrode prepared by the method of the present invention exhibits a higher current density, indicating that it has better catalytic performance.
[0039] EIS test results are shown in Figure 6 The results further confirm that the polarization resistance of the electrode prepared by the method of the present invention is significantly lower than the polarization resistance of the electrode prepared by the traditional aqueous solution impregnation method.
[0040] Example 2: Preparation of CeO2 nanoparticles and their application in solid oxide electrolysis cells
[0041] (1) Preparation of monodisperse CeO2 nanoparticle solution is the same as in Example 1;
[0042] (2) The preparation of the conventional electrode sheet is the same as in Example 1;
[0043] (3) After ultrasonicating the CeO2 nanoparticle solution for 10 min, use a 10 μL pipette to drop the CeO2 nanoparticle solution onto the fuel electrode of the electrode sheet, dripping 5 μL each time for 6 times, with a total dripping and impregnation of 30 μL. After drying in an oven at 80°C for 30 min, calcinate in a muffle furnace at 400°C for 1 h.
[0044] (4) Electroreduction of CO2 in solid oxide electrolysis cells
[0045] Step (3) After the electrode disc is calcined, silver paste is brushed on the fuel electrode and the air electrode as a current collecting layer, and baked in an oven at 150°C for 30 minutes. Silver wire is used as a conductor for the fuel electrode and the air electrode. The prepared electrode disc is placed at one end of a ceramic tube with the fuel electrode facing inward and in contact with the gas in the tube, and the air electrode is exposed to the air, and sealed with ceramic glue;
[0046] After N2 was purged at the other end of the ceramic tube, N2 containing 95% CO2 was introduced into the ceramic tube as the raw gas, and the electrolysis of CO2 was carried out at the fuel electrode. The raw gas flow rate was 30 mL / min, and the temperature was increased to 800°C at 3°C / min for testing;
[0047] IV test results are shown in Figure 7 From the figure, it can be seen that the current density is 2.84A·cm at 800℃ and 1.6V. -2 .
[0048] In summary, the electrode prepared by the method of the present invention using a monodisperse CeO2 nanoparticle n-hexane solution exhibits higher electrocatalytic performance in the SOEC electroreduction of CO2 process, provides a new method for improving the performance of SOEC, and has important application value in the field of efficient energy conversion and storage technology.
Claims
1. Application of monodisperse oxide nanoparticles in a solid oxide electrolytic cell, characterized in that: A monodisperse oxide nanoparticle n-hexane solution is prepared by thermal decomposition, and the monodisperse oxide nanoparticle n-hexane solution is dropped onto a fuel electrode to allow it to be immersed in the fuel electrode. After drying, the solution is calcined at 350-450°C for 1-2h to obtain an oxide nanoparticle-modified fuel electrode. The modified fuel electrode is used in the electroreduction of CO2 in a solid oxide electrolyzer to improve the catalytic efficiency of the electroreduction of CO2 reaction.
2. The use according to claim 1, characterized in that: The metal oxide nanoparticles are monodispersed CeO2 nanoparticles.
3. The use according to claim 2, characterized in that: The monodisperse CeO2 nanoparticle n-hexane solution is prepared by stirring ammonium cerium nitrate, 1-octadecene and a surfactant in an inert atmosphere, treating at 175-185°C for 1.5-2.5 hours, cooling to room temperature, adding anhydrous ethanol and centrifuging for 3-4 times, separating the solid and the liquid, washing the solid with anhydrous ethanol for 1-2 times, and dispersing the solid in an n-hexane solvent.
4. The use according to claim 1, characterized in that: The fuel electrode is a perovskite material electrode, and the perovskite material is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ or La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3-δ .
Citation Information
Patent Citations
Method for manufacturing CeOCl nano-particles
CN102583494A
Catalyst nanoparticle dispersion liquid and preparation method and application thereof
CN107335416A
High-efficiency and high-CO-yield porous fuel electrode for solid oxide electrolytic cell as well as preparation method and application of high-efficiency and high-CO-yield porous fuel electrode
CN118223062A